Traffic analysis at a multileged intersection in Osun State, Nigeria (2019)
Transportation system plays an important role in modern life throughout the universe; however, the undesirable myriad of traffic congestion has caused a number of problems in the society. This study aimed at evaluating the flow of traffic at Okefia intersection in Osun State. The present level of service was obtained to evaluate the road capacity. The traffic volume survey of the intersection was done using manual count procedure, volumes were taken at peak period of the day for 7 days at each approach, the peak hour factor was used to obtain the level of service. Approaches A and B were dual carriage with lane width of 7.3m each at both bound separated by a kerb, approaches C, D and E are single carriageways with road widths of 7.3m, 6.5m and 5.5 respectively. The average traffic volume counts for the 7 days at peak hour was 2632,2517, 625, 3197 and 1694 veh/hr for approaches A, B, C, D, and E respectively. Therefore, the average peak hour factor at the intersection is 0.83 and this corresponds to an overall level of service (LOS) C. This LOS implied that there will be delay between 15.1 and 25.0 seconds per vehicle and thus witnessed longer cycle lengths and fair progression. In order to reduce congestion and to improve the road capacity there is need to build good parking facility and introduce traffic control system.